Cross Type Neutralizing Antibodies Detected in a Unique HIV-2 Infected Individual From India - Vidyavijayan, K. K.; Cheedarala, Narayanaiah; Babu, Hemalatha; Precilla, Lucia K.; Sathyamurthi, Pattabiraman; Chandrasekaran, Padmapriyadarsini; Murugavel, Kailapuri G.; Swaminathan, Soumya; Tripathy, Srikanth P.; Hanna, Luke Elizabeth (Frontiers in Immunology, 2018)
Background: HIV-2, a retrovirus that is closely related to HIV-1, is characterized by slower disease progression and transmission, longer latency period and low or undetectable viremia. Host immunity, including production of potent neutralizing antibodies, may be one of the possible contributors to the distinction between the two infections. In an attempt to understand whether HIV-2 inection elicits production of neutralizing antibodies and to characterize the nature of the neutralization response we screened plasma of 37 HIV-2 infected individuals for the presence of broadly neutralizing antibodies. Materials and Method: Thirty seven asymptomatic, ART-naïve, HIV-2 infected individuals were recruited for the study. Plasma obtained from these individuals were screened for the presence of broadly cross reactive neutralizing antibodies (BCNabs) using the standard neutralization screening protocol with a panal of HIV-1 and HIV-2 pseudoviruses. Plasma exhibiting broad neutralization activity were assessed for their potency employing a titration assay. Further,an attempt was made to characterize the neutralization specificity of the plasma exhibiting broad and potent neutralization ability. Result: While majority of the samples tested were capable of neutralizing HIV-2 pseudoviruses with high to moderate potency, one unique sample demonstrated broad cross clade and cross type neutralization with ability to strongly neutralize the vast majority of both HIV-1 and HIV-2 viruses tested (19/20). Preliminary analyses indicate the possible presence of antibodies with multiple glycan epitope binding specificities. Conclusion: The study identified a unique HIV-2 sample with exceptional ability to neutralize HIV-2 viruses and cross-neutralize HIV-1 viruses with great breadth and potency. This sample holds promise for isolation of novel monoclonal antibodies that may exploited as potential therapeutic tools for HIV infection.